Tinjauan Kriminologis Terhadap Pelaku Tindak Pidana Penyebaran Hoax Kasus Sunda Empire - ilham nurfaizi kurniawan; Benny Irawan; Rena Yulia (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
The spread of hoaxes in Indonesia is currently increasingly widespread and is often carried out by the Indonesian people to make others believe in an event and an information that does not have actual facts, with the circulation of this hoax news will be bad for the development of the State of Indonesia in the future. This study is to find out what factors cause the occurrence of the crime of spreading hoaxes in the Sunda Empire case and what efforts need to be made to prevent the crime of hoaxes in the Sunda Empire. The research method used is the normative juridical method, namely by examining library legal materials or secondary data, namely data that refers to legal norms in laws and regulations, legal theories and court decisions which are then analyzed qualitatively. The results of this study indicate that what factors lead to the emergence of the crime of spreading hoaxes in the Sunda Empire case in a criminological perspective due to the ego aspect which is more inclined to the id aspect so that the superego aspect is weak and unable to balance the mind in tackling inner conflicts that occur so that make the crime of spreading the Sunda Empire hoax. if not immediately prevented, it will cause more victims to be affected than.